Requirements, Criteria, Challenges, and Solutions for the Internationalization of Medical Education in Iran: A Qualitative Study - Salman Bashzar; Vahid Feyzabadi; Atefeh Ahmadi; Fatemeh Karami Robat; Masoomeh Shahsavari; Ali Akbar Haghdoost; Bagher Amirheidari (Strides in Development of Medical Education, 2023)
Background: Despite some obstacles, internationalization of medical education can promote the educational, research and clinical level of universities.Objectives: The purpose of this study was to explore the opportunities, challenges, and solutions of the internationalization of higher medical education in Iran.Methods: The present qualitative study was conducted with Brown and Clark's thematic content analysis approach. Purposeful sampling was performed using the snowball strategy, and the data were collected using semi-structured interviews. The statistical population included Iranian students and professors residing in universities abroad, experts and key officials working in the Deputy of International Relations in Iran’s Ministry of Health and Medical Education, the Vice-Chancellors of the International Relation Units of the country’s universities of medical sciences, and foreign students studying in Iran’s universities of medical sciences. The data were gathered by conducting 17 interviews with eligible individuals following the principle of data saturation. Finally, the data were subjected to thematic analysis by MAXQDA-10 software.Results: The data extracted from the interviews were categorized into 268 codes, 29 subcategories, and six categories. The themes identified were "specifications of an international higher education center", "advantages of internationalization", and "necessary items and requirements" in the field of requirements and criteria, "weaknesses and challenges of internationalization" in the field of challenges, "operational solutions for addressing challenges" and "successful domestic and foreign experiences of the internationalization of higher medical education centers " in the field of solutions. The subthemes of "weaknesses and challenges at the level of the university" and "hardware specifications" attained the highest frequency among open codes.Conclusion: A need to be responsive to many present and future needs of our country necessities that the higher medical education system moves in parallel with the globalization process and multicultural societies. In this regard, officials should pay attention to the requirements, criteria, challenges, and solutions of the internationalization of higher medical education in Iran based on the evidence disclosed in this study.